Stimulating agritourism loyalty in the Mid-Atlantic states of the USA - Rahmiye Figen Ceylan; Ramu Govindasamy; Burhan Ozkan; Sonal Pandey (Tourism)
Agritourism as a niche tourism market has become an alternative income-generating sector for conventional farmers that focus on both production and marketing. Agritourist activities involve joining production and harvest, receiving education and on site-training. However, unless individuals endeavor and they consistently demand these activities, agritourism cannot be promoted among farm operators. In other words, agritourism is a demand-driven sector and requires the loyalty of participants which was measured with respect to more than a single take up of agritourism in the past two years. With this research, the loyalty of agritourists and the factors affecting their persistent participation were estimated based on a sample from the Mid-Atlantic states of the USA. The findings infer that agritourism loyalty is stimulated by the rising level of agritourist education and increasing income. Married people with children also prefer rural participation. Agritourists, who have the potential to become loyal, focus above all on buying fresh and high-value products. Following this, they demonstrate a rising tendency to learn about agricultural production, and to spend quality time with family/friends. These results suggest that with proper marketing strategies, supportive actions designed for farmers that seek alternative income, and the involvement of regional/local authorities in decision making and promotional processes, may contribute to the development of agritourism and expand its market through assuring customer loyalty.